Species co‐occurrences in ectoparasite infracommunities: Accounting for confounding factors associated with space, time, and host community composition. (16th June 2020) - Krasnov, Boris R.; Stanko, Michal; Lareschi, Marcela; Khokhlova, Irina S.
Abstract : 1. We explored patterns of co‐occurrence of ectoparasite species on individual hosts from Central Europe (Slovakia) and South America (Argentina) within and between higher taxa while controlling for confounding factors associated with variation between host individuals and host species, as well as spatial and temporal variation. We used a recently developed statistical approach, the hierarchical modelling of species communities. 2. Although the probability of pairwise associations of the majority of species in both regions did not differ from random, all significant species associations in Slovakia were positive, whereas the only three significant species associations in Argentina were negative. On average, associations between ectoparasite species belonging to different higher taxa were positive in Slovakia and negative in Argentina. 3. At the host species level, both positive and negative associations between species were detected in all higher taxa. This was also true for ectoparasite co‐occurrences in the same site, habitat, or year; although the number of co‐occurring species pairs with high posterior probability was much greater in Slovakia than in Argentina. 4. We conclude that consideration of species co‐occurrences across the entire multi‐host assemblage and control for confounding spatial and temporal factors provided important insights into parasite community structure. Abstract : Associations of ectoparasite species on individual hosts were mostly positive, although this pattern was more pronounced in European than South American assemblages. Ectoparasite species associations in the same host species, site, habitat, and year could be either positive or negative, with the number of significantly associated pairs being greater in European than South American ectoparasites. Controlling for confounding spatial and temporal factors and consideration of species co‐occurrences across multi‐host assemblages provides important insights into parasite community structure.